“It is untranslatable, but we try hard”: Translators and Translation Experts on the Current Problems of Translation Theory and Practice - Varshaver , Olga; Gonzalez , Alejandro Ariel; Kuznetsova , Tatiana; Petrova , Elena; Sidorova , Olga; Hewitt , Karen (Quaestio Rossica, 2023)
This paper summarises the materials of the discussion devoted to the role and specificity of artistic translation in the contemporary world, which was held in the summer of 2023. The participants of the discussion are specialists from Argentina, the UK, and Russia (Moscow, St Petersburg, and Yekaterinburg), all of whom are active translators, as well as researchers, lecturers, and translation editors. The participants received questions they were offered to answer, and their written responses make up the text of the article. The article is relevant, as today, the role of translation is increasing, and translation theory is one of the dynamically developing areas of modern scholarly knowledge. The contributors examine such topical issues of translation theory as translatability/non-translatability, didactics of translation, and the reliability of the source base for translation. The discussion also considers the role of new translations of classical literary works whose earlier translations have already entered the receiving culture, and translations meant for different groups of readers. Additionally, the contributors of the article express their views on the identity of the translator, on what it means to be a “good translator”, the requirements and demands that are placed upon them.